An economic evaluation on FRP for bridge construction in South African coastal areas - Ndeutapo, Samuel (Department of Civil Engineering, 2023)
Fibre Reinforced Polymers (FRP) have been used for approximately 30 years as concrete strengthening materials in structural applications. This is primarily due to Steel Reinforced Concrete (SRC) being susceptible to the corrosion of reinforcing steel, especially in coastal environments. However, the use of FRP composites for bridge construction is faced with challenges. These challenges arise from uncertainties regarding the high material and initial construction costs. Additionally, there is limited research available on the costs involved when incorporating the fibres in bridge constriction. It then becomes critical to understand the life cycle costs of FRP in bridge construction. Furthermore, suitable economic and deterioration models can be used to predict these life cycle costs by employing a LCCA. The research aim was to investigate the economic viability of using FRP as reinforcing elements in bridge construction. This was done by conducting a life cycle cost analysis (LCCA) on two highway beam bridge superstructure designs: a SRC superstructure and a GFRP-RC superstructure to determine the preferred design, which was used to conclude on the economic viability of FRP in bridge construction. The deterministic approach to the LCCA was selected and the outcome was expressed in terms of Present Worth of Costs (PWOC). The initial construction costs were found to be the bulk, while the disposal costs were the least of the total LCC for both superstructure alternatives. Furthermore, initial construction costs of the SRC superstructure were found to be less than that of the GFRP-RC superstructure, by a margin of R 873 094. This was primarily due to the cost of E-glass reinforcement, approximately 2.1 to 2.9 times more expensive than the cost of steel reinforcement. Moreover, the cost of GFRP was seen to have decreased over the years. LCC savings were seen from the GFRP-RC superstructure over the SRC superstructure, by a margin of R4 627 830 in terms of maintenance costs. This was mainly due to the application of a corrosion inhibitor (concrete surface treatment) and the use of a cathodic protection system on the SRC bridge superstructure. Furthermore, the GFRP-RC superstructure was found to be the least cost-effective investment from approximately 34 years of a 75 year LCCA period. At the end of the analysis period, the SRC bridge superstructure was found to have cost savings of approximately R 753 921 in PWOC over the GFRP-RC superstructure. Furthermore, a sensitivity analysis of the various input costs and discount rates of the LCCA was also conducted. Initial construction costs were found to have the highest positive correlation on the outcome of the LCCA. The other costs and as well as the discount rate were all found to have an insignificant effect on the outcome of the LCCA. It was concluded that it was not economically viable to include FRP as reinforcing elements in bridge construction at the time. However, since the cost of FRP was seen to decrease over time, the inclusion of FRP rebars in bridge construction might be economically viable in the future.